Seroepidemiologic study of giardiasis patients and high-risk groups in a midwestern city in the United States. - Sullivan, R (1987)
Serum antibodies to Giardia lamblia were measured in giardiasis patients, in groups at high risk for intestinal parasite infection, and in controls by an indirect fluorescent antibody (IFA) technique. Symptomatic patients had the highest antibody titers, and antibodies remained present for up to 18 months in persons with chronic infection. Indochinese refugees and male homosexuals with the acquired immunodeficiency syndrome (AIDS) and pre-AIDS had higher mean antibody levels than did healthy controls, whereas sewer and highway maintenance workers had levels similar to those of controls. Serum antibodies to Entamoeba histolytica measured by an indirect hemagglutination antibody technique were detected in only a few Indochinese refugees. We conclude that serology is a promising tool in G. lamblia epidemiology and that further population studies would be of interest.